Advances in usability, user experience and assistive technology : proceedings of the AHFE 2018 International Conferences on Usability & User Experience and Human Factors and Assistive Technology, held on July 21–25, 2018, in Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA /: proceedings of the AHFE 2018 International Conferences on Usability & User Experience and Human Factors and Assistive Technology, held on July 21–25, 2018, in Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA. ([2018]) - Unknown
No abstract available